The Effect of Inner Fan Blade Angle to The Ventilation Rate of The Turbine Ventilator - Setiawan, Priyo Agus; Yuwono, Triyogi (Jurnal Rekayasa Mesin, 2018)
Geographical location of Indonesia country has relative wind speed lower than the countries of turbine user e.g. Finland, United States of America, and other countries. Turbine ventilator can be used as ventilation within wind energy driver. The turbine ventilator generates drag force and causes rotated turbine ventilator. This rotation generates a negative pressure inside turbine ventilator and inhaled air. The previous study revealed that the performance of turbine ventilator signifies at low wind speed. Indonesia has low wind speed, thus it should be relevant to assemble the additional inner fan in turbine ventilator. The research method was applied by conducting the experiment to test the effectiveness of turbine ventilator placed above plenum 1 m x 1 m x 2.3 m. NACA 0015 was used for blade inner fan with a variety of inner fan blade angles 15o, 30o, 45o and 60o and varied wind speed to turbine ventilator 1.5, 3, 4.5 and 6 m/s. The turbine ventilator used in this research was about 18 inches in size to measure flow rate over the plenum. Inner fan rotated at 500 rpm. The results of the experiment reveal that rotating turbine ventilator increased the flow rate at an inner fan blade angle of 45 degrees and maximum ventilation rate was at inner fan blade of 45 degree angle.